Development of control algorithm for a new 12s-6p single phase field excited flux switching motor - Amin, Faisal (2020)
Flux switching motor (FSM) fall into a special category of switch reluctance motors (SRM). One of the key features of FSM is its rotor structure. Generally, it is free from any magnet and winding. Thus, allowing the motor to attain considerably higher speed and more stability then conventional AC motor. However, this simple and robust structure demands more sophisticated driving mechanism mainly due to the absence of rotating magneto motive force (MMF) in the rotor. The main concern of this research is to design algorithms for starting and driving 12 slots and 6 poles (12S-6P) segmental rotor field excited flux switching motor (FEFSM) and evaluate the algorithms efficiency by analyzing motor’s dynamic performance in terms of torque and current consumption. In this research, two algorithms have been proposed in which first algorithm is based on bipolar DC signals while second algorithm is based on field oriented control (FOC) principle. For position detection, algorithms merely need a basic infrared transceiver sensor. Bipolar DC signal algorithm is based on changing the polarity of armature DC voltage on the detection of zero rotor position. On the other hand, FOC algorithm involves detection of rotor zero position to estimate speed and prediction of instantaneous rotor position in real time. Initially, fundamental control principle for 12S-6P FEFSM has been identified through the finite element analysis (FEA) of the model. Afterwards control algorithms have been successfully developed and implemented in the motor control hardware. Compared to Bi-polar DC algorithm, the observations shows that the single phase FOC algorithm results in far less distortion of armature voltage waveforms even at high speed, which results in jittering free motor operation. On the other hand, Bi-polar DC algorithm results in much higher torque production, which is about 50% more than that of the single phase FOC’s yield. In terms of simulation and prototype performance comparison, Bi-polar DC algorithm is about 92% efficient in torque generation in case of initial model of FEFSM and staggering efficiency around 96% in case of optimized motor model.